2017
DOI: 10.1002/cbic.201700382
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Fluorinated A2A Adenosine Receptor Agonist with Application to Last‐Step Enzymatic [18F]Fluorination for PET Imaging

Abstract: The A adenosine receptor belongs to a family of G-coupled protein receptors that have been subjected to extensive investigation over the last few decades. Due to their prominent role in the biological functions of the heart, lungs, CNS and brain, they have become a target for the treatment of illnesses ranging from cancer immunotherapy to Parkinson's disease. The imaging of such receptors by using positron emission tomography (PET) has also been of interest, potentially providing a valuable tool for analysing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…With both 12 and 13 to hand, our attention turned to further assembly through Sonogashira cross‐coupling. This was accomplished by using an excess of 12 over 13 in the Pd 2 (dba) 3 ‐catalysed reaction. The ClDA‐PEG‐ester 14 was recovered in high purity after chromatography and C 18 cartridge purification.…”
Section: Resultsmentioning
confidence: 99%
“…With both 12 and 13 to hand, our attention turned to further assembly through Sonogashira cross‐coupling. This was accomplished by using an excess of 12 over 13 in the Pd 2 (dba) 3 ‐catalysed reaction. The ClDA‐PEG‐ester 14 was recovered in high purity after chromatography and C 18 cartridge purification.…”
Section: Resultsmentioning
confidence: 99%
“…Shimada et al have identified that xanthine bearing the styryl group showed selective A 2A R antagonistic properties (Schiffmann et al, 1991), and KF17837, a ligand with superior selectivity and potent affinity for A 2A Rs, was optimized for the development A 2A R PET tracers (Seale et al, 1988). At present, several PET tracers were reported, such as [11C]TMSX ([11C]KF18446) (Ishiwata et al, 2000a;Ishiwata et al, 2003b) (Wang et al, 2000) and [18F]MDMPC (Lowe et al, 2017), and were investigated as promising PET agents (Ishiwata et al, 1996;Stone-Elander et al, 1997;Wang et al, 2000). In addition, [11C]TMSX (formally designated as [11C]KF18446) was selected for medical applications (Ishiwata et al, 2005).…”
Section: Development Of Xanthine Based a 2a R Positron Emission Tomogmentioning
confidence: 99%
“…Recently, different pre-targeting strategies have been developed for treatment and imaging of different diseases. Those include e.g., radiolabeling of the human A2A adenosine receptor [169], a prostate cancer-related membrane protein [170] or the combined application of biotin and tetrazine-conjugate with antibodies [171]. In all cases, it was shown that the fluorinase (FlA) accepts substrates with different moiety at C-2 of the adenine ring.…”
Section: Metal-free Haloperoxidases/perhydrolasesmentioning
confidence: 99%